Information science and its correlated areas: a case sudy at the Federal University of Minas Gerais - Fernandes, Wesley Rodrigo; Cendón, Beatriz Valadares; Araújo, Carlos Alberto Ávila (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2012)
This research contributes to the understanding of what Information Science is and how it is evolving by verifying the disciplines Information Science interacts with at the present time, as well as the breadth and intensity of these relationships. The research uses two bibliometric studies of the scientific journals utilized by researchers in the field. In the first study, citation analysis assessed 433 journals cited in the bibliographies of 18 theses and 39 dissertations from the Graduate Program of Information Science of the Federal University of Minas Gerais. These were first examined to determine their distribution in nine categories representative of large areas of knowledge. Next, subareas to which each journal pertained were also identified. In the second study, 316 journals from the field of Information Science, which the CAPES Portal of Scientific Journals subscribed to, were identified and analyzed in terms of the other areas of knowledge to which they were also designated by the Portal. The results of the citation analysis revealed that 31.8% of 433 journals cited were interdisciplinary, 49.7% pertained to other areas of knowledge while 18.50% were classified solely as Information Science. The analysis of the data from second study revealed that 57% of the journals were classified solely as Information Science and 43% were classified simultaneously in more than one area. Results stemming from both studies show that computer science, administration and education are the disciplines most closely related to Information Science. The areas of knowledge to which Information Science most broadly relates are applied social sciences, human sciences and linguistics, literature and the arts. Keywords: Information Science. Interdisciplinarity. Correlated Knowledge Areas. Bibliometric Study. Link para o texto completo (PDF) http://www2.marilia.unesp.br/revistas/index.php/bjis/article/viewFile/1260/1472